2017
DOI: 10.5430/jer.v3n1p57
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and perceptions on genetically modified mosquitoes: Case for sterile mosquito release in Grenada

Abstract: This study assessed knowledge, attitudes and perceptions of various stakeholders in Grenada regarding genetically modified organisms and the release of genetically modified mosquitoes. The study adopted a cross sectional design with a study population that comprised of members from seven stakeholder groups of civil society in Grenada. The sample population was obtained through a snowballing strategy and data collection for the study consisted of a semi-structured interview. Data was managed through the collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…While previous studies have reported a high level of knowledge about malaria symptoms, prevention, and treatment among different stakeholder groups across Africa [39][40][41][42], this study revealed some gaps in understanding of the current malaria situation, especially among key decision makers in the continent. Nearly half of the survey respondents in this study could not indicate reasonable estimates of the malaria burden in their countries.…”
Section: Discussionmentioning
confidence: 62%
“…While previous studies have reported a high level of knowledge about malaria symptoms, prevention, and treatment among different stakeholder groups across Africa [39][40][41][42], this study revealed some gaps in understanding of the current malaria situation, especially among key decision makers in the continent. Nearly half of the survey respondents in this study could not indicate reasonable estimates of the malaria burden in their countries.…”
Section: Discussionmentioning
confidence: 62%